Religious Parenting Practices and Moral Socialization in Muslim Families: A Case Study of Sungai Duren Village - Puspita Sari, Pitra; Saadah, Lailis; Ine Robi’ah, Fitri; Solikhah, Solikhah; Ervina, Dina; Iqbal Haqim Mohd Nor, Mohd (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Religious socialization in rural Muslim families remains insufficiently examined, particularly regarding how Islamic values are sustained amid economic constraints and the growing presence of digital entertainment in children’s everyday lives. This study investigates religious parenting practices and moral socialization in Muslim households in Sungai Duren Village, Jambi Luar Kota District, Muaro Jambi Regency. Employing a qualitative case-study design, data were generated through semi-structured in-depth interviews, naturalistic observations, and document analysis during six months of fieldwork with 18 purposively selected informants, including parents, local religious educators, and community figures. The data were analysed thematically, drawing on Religious Socialization Theory alongside Social Learning and Ecological Systems perspectives. The findings show that children’s moral–religious formation is sustained through interconnected practices of worship discipline, parental modelling, and the continuity of learning across home, TPQ, and mosque activities. However, these processes are shaped by structural and everyday constraints, including limited parental religious literacy, economic pressures, and children’s smartphone use that disrupts routine discipline and weakens parental mediation. Community religious institutions play a reinforcing role by stabilising practices and providing moral guidance when household resources are limited. By demonstrating how religious socialization operates as an ecologically coordinated process across family and community settings, this study contributes to broader discussions on Islamic parenting and moral education in contemporary rural contexts.